119 Original research. (19th September 2017) - Zeoli, April; Frattaroli, Shannon; Kwiatkowski, Christine; Webster, Daniel
Abstract : Statement of Purpose: In this research, we assess the implementation of domestic violence-related firearm restrictions by local justice system actors, and determine factors that influence successful or unsuccessful surrender or removal. The restrictions under study are state laws prohibiting those under domestic violence restraining orders or those convicted of violent misdemeanour crimes from possessing firearms, and state laws specifying that prohibited individuals must relinquish their firearms for the duration of their prohibition. Methods/Approach: We conducted a cross-case comparative analysis of multiple local jurisdictions throughout the United States that represented a range of domestic violence restraining order firearm restriction laws and violent misdemeanour firearm restriction laws and enforcement strategies. Sabatier's theory of public policy implementation frames and informs this research. Key informant interviews were conducted with judges, prosecuting attorneys, law enforcement officers and domestic violence victim advocates. The interviews were transcribed and double-coded for reliability. Additionally, we examined relevant documents and processes, and data from administrative records related to the enforcement of firearm restrictions for each jurisdiction. Results will be presented, including discussions of the implications of the results. Significance and contributions to injury and violence prevention science: Multiple studies have analysed the impact of domestic violence-related firearm laws on domestic violence outcomes, but few have investigated the implementation of these laws. Use of the case study method will allow us to gain a rich understanding of how selected jurisdictions view and interpret the laws, the contexts in which the laws are enforced, and mechanisms and procedures associated with enforcement. The case studies are designed to create depth of understanding in selected sites and will inform theory for future research.